Evidence of Presynaptic Localization and Function of the c-Jun N-Terminal Kinase. (7th March 2017) - Biggi, Silvia; Buccarello, Lucia; Sclip, Alessandra; Lippiello, Pellegrino; Tonna, Noemi; Rumio, Cristiano; Di Marino, Daniele; Miniaci, Maria Concetta; Borsello, Tiziana
Abstract : The c-Jun N-terminal kinase (JNK) is part of a stress signalling pathway strongly activated by NMDA-stimulation and involved in synaptic plasticity. Many studies have been focused on the post-synaptic mechanism of JNK action, and less is known about JNK presynaptic localization and its physiological role at this site. Here we examined whether JNK is present at the presynaptic site and its activity after presynaptic NMDA receptors stimulation. By using N-SIM Structured Super Resolution Microscopy as well as biochemical approaches, we demonstrated that presynaptic fractions contained significant amount of JNK protein and its activated form. By means of modelling design, we found that JNK, via the JBD domain, acts as a physiological effector on T-SNARE proteins; then using biochemical approaches we demonstrated the interaction between Syntaxin-1-JNK, Syntaxin-2-JNK, and Snap25-JNK. In addition, taking advance of the specific JNK inhibitor peptide, D-JNKI1, we defined JNK action on the SNARE complex formation. Finally, electrophysiological recordings confirmed the role of JNK in the presynaptic modulation of vesicle release. These data suggest that JNK-dependent phosphorylation of T-SNARE proteins may have an important functional role in synaptic plasticity.